Characterization of biofilm formation in natural water subjected to low-frequency electromagnetic fields. Issue 3 (15th March 2016) - Mercier, Anne; Bertaux, Joanne; Lesobre, Jérôme; Gravouil, Kevin; Verdon, Julien; Imbert, Christine; Valette, Eric; Héchard, Yann
Abstract: Electromagnetic field (EMF) treatment has proven to be effective against mineral scaling in water systems. Therefore, it should be assessed for the treatment of other deposits such as biofilms. In this study, a commercial device producing low-frequency EMF (1–10 kHz) was applied to a reactor fed with natural water for 45 days. The treatment promoted the concentration of microorganisms in suspension and limited the amount of sessile microorganisms in the biofilm, as determined by the measurement of total DNA, qPCR and microscopy. The structure of the bacterial community was assessed by t-RFLP and pyrosequencing analysis. The results showed that EMF treatment affected both planktonic and sessile community composition. EMFs were responsible for a shift in classes of Proteobacteria during development of the biofilm. It may be speculated that the EMF treatment affected particle solubility and/or microorganism hydration. This study indicated that EMFs modulated biofilm formation in natural water.